Synthesis of substituted tryptanthrin via aryl halides and amines as antitumor and anti-MRSA agents. Issue 48 (29th November 2019) - Zheng, Xudong; Hou, Baolong; Wang, Rui; Wang, Yinyin; Wang, Cuiling; Chen, Huan; Liu, Li; Wang, Jilin; Ma, Xiumei; Liu, Jianli
Abstract: The natural alkaloid, tryptanthrin (indolo[2, 1-b]quinazoline-6, 12-dione), and its analogues are found to exhibit potent antitumor and anti -MRSA activities. An efficient and convenient method has been developed for the synthesis of tryptanthrin D-ring derivatives through the reaction of substituted tryptanthrins and secondary amines in moderate to good yields. Some of the new compounds exhibited antitumor activities against the human tumor cell lines A549, HCT116 and MDA-MB-231, with mean IC50 values at low micromolar levels. In addition, some of the compounds showed excellent anti -MRSA activities and were more effective than vancomycin, with MIC values of 0.31–1.25 μg/mL for Mu50, RN4220, and Newman strains. Graphical abstract: Image 1